A review on three‐dimensional graphene: Synthesis, electronic and biotechnology applications‐The Unknown Riddles. Issue 4 (15th March 2021) - Thiyagarajan, Pradheep
Abstract: In the last decade, carbon‐based nanostructures such as buckyball (C60 ), carbon nanotube (CNT), graphene and three‐dimensional (3D) graphene have been identified as promising materials for electronic, electrochemical energy storage (batteries and supercapacitors), optical and sensing applications. Since the discovery of graphene in 2004, scientists have devised mass production techniques and explored graphene as a promising material for a wide range of applications. Most of the electronic and solar cell applications require materials with good electronic conductivity, mobility and finite bandgap. Graphene is a zero bandgap material which prevents it from the mainstream applications. On the other hand, 3D graphene has good electronic conductivity, mobility, bandgap and electrochemical properties. This review article will focus on the synthesis of the 3D graphene, its structure‐property relationships, biotechnology and electronic applications and the hidden properties that are yet to be explored fully.